Rule Similarity and Axis Symmetry Patterns in Young Patients with Bilateral Astigmatism - Farrukh Mahmood; Hina Sharif; Mahmood Ali (Journal of the Pakistan Medical Association, 2022)
Objectives: To report rule similarity and axis symmetry patterns in young subjects with bilateral astigmatism. Methods: The cross-sectional study was conducted at Al-Shifa Trust Eye Hospital, Rawalpindi, Pakistan, from October 1, 2018, to March 31, 2019, and comprised diagnosed cases of bilateral astigmatism of either gender aged 15-45 years. After giving detailed ophthalmic history, all the participants underwent autorefraction followed by subjective refraction. Based on refractive status, rule similarity was categorised as isorule or anisorule, while axis symmetry was categorised as direct or mirror. Data was analysed using SPSS 20. Results: Of the 204 participants, 128(62.7%) were males and 76(37.3%) were females. The overall mean age was 26.64±8.44 years. Isorule astigmatism was present in 169(82.8%) participants, while 125(61.3%) had a mirror pattern of axis symmetry. Under the mirror and direct symmetry models, the medians of absolute difference in the axis of fellow eyes were 10 and 5 degrees respectively from exact symmetry. No significant association of rule similarity or symmetry of axis was found with age or gender (p>0.05), while significant association was found between rule similarity and type of astigmatism (p<0.001). Conclusions: Bilateral astigmatism of isorule category was found in majority of the participants, while mirror symmetry of the axis was more common than direct symmetry. Key Words: Astigmatism, Axis, Refractive errors, Rule similarity, Symmetry. Continuous...